Illiberal peace-building in Asia: a comparative overview. Issue 1 (2nd January 2020) - Smith, Claire Q.; Waldorf, Lars; Venugopal, Rajesh; McCarthy, Gerard
ABSTRACT: Over the past 20 years, there have been significant and historic breakthroughs in resolving protracted ethnic conflicts in restive regions of several states in South and South-East Asia. After decades of violence, Indonesia, Myanmar, Nepal, Sri Lanka, and Thailand have all witnessed periods of reduced conflict and increased stability. Peace-building as practiced in these states departs markedly from the liberal and post-liberal models in which Western actors and liberal norms play a key role. Here, by contrast, peace-building is driven by domestic actors applying illiberal norms and practices. In this introductory article, we trace the shift from liberal to post-liberal to illiberal peace-building, define illiberal peace-building, discuss the case studies presented in this special issue, and finally draw out common themes and policy implications.